2014
DOI: 10.1371/journal.pone.0107317
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Stain-Free and Continuous Multimodal Monitoring of Wound Healing In Vitro with Digital Holographic Microscopy

Abstract: Impaired epithelial wound healing has significant pathophysiological implications in several conditions including gastrointestinal ulcers, anastomotic leakage and venous or diabetic skin ulcers. Promising drug candidates for accelerating wound closure are commonly evaluated in in vitro wound assays. However, staining procedures and discontinuous monitoring are major drawbacks hampering accurate assessment of wound assays. We therefore investigated digital holographic microscopy (DHM) to appropriately monitor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 61 publications
(80 reference statements)
0
52
0
Order By: Relevance
“…33 It has been shown that the measured phase in the image corresponds to the dry mass density distribution within the cell. 26,27 In contrast to existing DHM techniques, 4,7,18,19 the use of incoherent illumination enables high-quality quantitative phase imaging with strong suppression of coherent noise and parasitic interferences while providing high temporal stability and spatial uniformity of the phase measurement. 25 Using the approach described in Ref.…”
Section: Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 It has been shown that the measured phase in the image corresponds to the dry mass density distribution within the cell. 26,27 In contrast to existing DHM techniques, 4,7,18,19 the use of incoherent illumination enables high-quality quantitative phase imaging with strong suppression of coherent noise and parasitic interferences while providing high temporal stability and spatial uniformity of the phase measurement. 25 Using the approach described in Ref.…”
Section: Image Acquisitionmentioning
confidence: 99%
“…Assessment of wound healing by monitoring the cellular volume, dry mass, and refractive index was presented in Ref. 19. The study of cancer cell growth and drug response by monitoring cell dry mass is described in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the averaged phase contrast ϕ Δ caused by the cells in the area S c and the corresponding average cell thickness d was retrieved. Finally, from the parameters S c and ϕ Δ the change of the cellular dry mass DM, which is related to the intracellular protein content [35], was retrieved as described in [36] following an approach in [37]. Figure 5(b) shows that the area S c covered by the cells is underestimated for the quantitative phase images from single holograms in comparison to the averaged phase images from modulated illumination for periods in which the cells adhere thin on the Petri dish bottom.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, DH microscopy analysis opens a novel diagnostic option for optical quantification of inflammation in murine models of colitis. Moreover, the same research group assessed cellular growth and motility in epithelial wound healing in vitro using DH microscopy [53]. Interestingly, phase images quantifying cell thickness, dry mass, and tissue density were demonstrated.…”
Section: Quantification Of Inflammationmentioning
confidence: 99%